2021
DOI: 10.3390/cells10030678
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Driven Effects in Cancer: Characterization, Mechanisms, and Therapeutic Implications

Abstract: Hypoxia, a common feature of solid tumors, greatly hinders the efficacy of conventional cancer treatments such as chemo-, radio-, and immunotherapy. The depletion of oxygen in proliferating and advanced tumors causes an array of genetic, transcriptional, and metabolic adaptations that promote survival, metastasis, and a clinically malignant phenotype. At the nexus of these interconnected pathways are hypoxia-inducible factors (HIFs) which orchestrate transcriptional responses under hypoxia. The following revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 240 publications
0
52
0
Order By: Relevance
“…In xenograft mouse models, tumour growth and angiogenesis are associated with HIF-1α expression. In addition, HIF-1α protein synthesis is controlled by promoting the PI3K/Akt and extracellular signal-regulated kinase (ERK)/MAPK-signalling pathways and is involved in tumour growth ( Majmundar et al ., 2010 ; Shi et al ., 2021 ). Similar findings have been reported in studies on ovarian and brain cancers and indicated a regulatory role of HIF-1α in initiating angiogenesis via interactions with pro-angiogenic factors such as VEGF ( Zagzag et al ., 2000 ; Birner et al ., 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…In xenograft mouse models, tumour growth and angiogenesis are associated with HIF-1α expression. In addition, HIF-1α protein synthesis is controlled by promoting the PI3K/Akt and extracellular signal-regulated kinase (ERK)/MAPK-signalling pathways and is involved in tumour growth ( Majmundar et al ., 2010 ; Shi et al ., 2021 ). Similar findings have been reported in studies on ovarian and brain cancers and indicated a regulatory role of HIF-1α in initiating angiogenesis via interactions with pro-angiogenic factors such as VEGF ( Zagzag et al ., 2000 ; Birner et al ., 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, relevant classifiers are still in great demand for guiding clinical treatment or predicting prognosis. Hypoxia, a kind of tumor microenvironmental stress related to poor prognosis of patients, is a hallmark of solid tumors, 39 and immune cell infiltration characterizations are also a research hotspot in many solid tumors. 40 Most classifications focus on a single biological and molecular feature and in this study, a new classifier was developed by combining the hypoxic state and immune cell infiltration of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia-inducible factor 1α (HIF-1α) is the pivotal transcription factor of response to hypoxia and a key regulator of many genes that drive both types of hypoxia-triggered cellular mechanisms, such as cancer development and invasion and immunosuppression [ 87 ]. To fix insufficient oxygen supply, HIF-1α regulates the signaling of angiogenesis pathways and promotes vascularization of tumors, increasing the expression of proangiogenic factors such as vascular endothelial growth factor A, platelet-derived growth factor subunit A, transforming growth factor-β and angiopoietin-like 4 [ 88 , 89 ].…”
Section: Hypoxia and Metabolismmentioning
confidence: 99%
“…Thus, hypoxia represents a negative prognostic factor and correlates to aggressiveness, metastatic progression and therapeutic resistance of tumors, as described in several reviews [ 91 , 92 , 93 ]. Indeed, HIF-1α regulates the expression of specific genes involved in the invasion, as fibronectin 1, lysyl oxidase-like 2, urokinase plasminogen activator receptor, epithelial–mesenchymal transition-associated transcription factors ZEB, SNAIL and TWIST [ 87 ].…”
Section: Hypoxia and Metabolismmentioning
confidence: 99%